Myopia control efficacy of spectacle lenses with highly aspherical lenslets: results of a 5-year follow-up study - Xue Li; Yingying Huang; Chenyao Liu; Xindan Chang; Zaifeng Cui; Qiulin Yang; Björn Drobe; Mark A. Bullimore; Hao Chen; Jinhua Bao (Eye and Vision)
Abstract Purpose To evaluate myopia control efficacy in myopic children wearing spectacle lenses with highly aspherical lenslets (HAL) for 5 years. Methods This is a randomized, double-masked extended trial. Myopic children aged 8 to 13 years who were originally allocated to the HAL group in the 2-year clinical trial. The HAL group underwent a 5-year assessment for myopia progression using cycloplegic spherical equivalent refraction (SER) and axial length (AL). An extrapolated single-vision spectacle lenses (ESVL) group was used as a control group. The 5-year myopia progression and axial elongation of the ESVL group was calculated based on the 2-year data from the single-vision spectacle lenses group in the same clinical trial, and the data for the following 3 years was estimated by assuming an annual reduction in SER by 9.7% and in AL by 15%. A generalized linear model approach was used to evaluate the treatment efficacy. The validity of the ESVL group was evaluated by comparing myopia progression in the first year of the 3-year estimates with a single-vision spectacle lenses (SVL2) group from a 1-year extended study of the same clinical trial. Results Forty-three participants from the original HAL group completed the 5-year visit (74%). Five-year myopia progression [mean ± standard error (SE)] in the HAL group was − 1.27 ± 0.14 D. Compared with the ESVL (− 3.03 ± 0.18 D), myopia progression was − 1.75 ± 0.24 D less for the HAL group (P < 0.001). The mean AL elongation over 5 years was 0.67 ± 0.06 mm for the HAL group compared with 1.40 mm in the ESVL group (P < 0.001), AL elongation was slower by 0.72 ± 0.10 mm for the HAL group (P < 0.001). No significant differences were found for myopia (− 0.58 ± 0.04 D vs. − 0.56 ± 0.05 D) or AL elongation (0.28 ± 0.02 mm vs. 0.28 ± 0.02 mm) between the ESVL group and SVL2 group (P SER = 0.83; P AL = 0.93) in year 3. Conclusions In this 5-year study, HAL spectacles reduced the rate of myopia progression and axial elongation, preventing the equivalent of 3 years of myopia progression and axial elongation. Long-term use of HAL spectacles also decreased the incidence of high myopia. Extrapolated control groups are valid for evaluating myopia progression in long-term studies. Trial registration The study was registered at the Chinese Clinical Trial Registry (ChiCTR2100047262), https://www.chictr.org.cn/showproj.html?proj=127182 .